Investigating the effects of percussion massage therapy on pain, functionality, kinesiophobia, and quality of life in individuals with non-specific low back pain (Annals of Medical Research, 2025)
Aim: This study aimed to investigate the effects of percussion massage therapy applied to the paravertebral muscles on pain, functionality, flexibility, kinesiophobia, and quality of life in individuals with mechanical low back pain.Materials and Methods: The study enrolled 40 individuals diagnosed with non-specific low back pain. Participants were randomly assigned to one of two groups: percussion massage therapy (PMT) or conventional therapy (CT). Both groups participated in a 6-week treatment program. Pain levels were evaluated using the Visual Analog Scale (VAS), functionality was assessed with the Oswestry Disability Scale (ODS), flexibility was measured via the Sit-and-Reach Test, kinesiophobia was assessed using the Tampa Scale for Kinesiophobia (TSK), and quality of life was measured with the Short Form-36 (SF-36). Assessments were performed both before and after the treatment period. The CT group engaged in exercises focused on strengthening, stabilization, and stretching of the lumbar region, while the PMT group received percussion massage therapy targeting the paravertebral muscles in addition to conventional physiotherapy.Results: Post-treatment, both groups significantly improved all assessment parameters (p
Keywords: Exercise; Mechanical low back pain; Local vibration; Percussion massage therapy